Equalizing MELD Scores Over Broad Geographies Is Not the Most Efficacious Way to Allocate a Scarce Resource in a Value-based Environment. Issue 2 (August 2015) - Reed, Alan; Chapman, William C.; Knechtle, Stuart; Chavin, Kenneth; Gilroy, Richard; Klintmalm, Goran B. G.
<x xml:space="preserve">Abstract</x> The proposed redistricting policy, meant to equalize MELD at transplant across broad geographies in the belief that this will equalize wait list and post-transplant mortality rates, ignores the concept of resource management. Choosing to allocate livers primarily to the "sickest first, " no matter where they live, will impact transplantation in a number of ways, some not yet tested. The Final Rule, however, emphasizes utility in its many elements and not only geography. The geographic focus leaves post-transplant outcomes, costs, and other critical issues undefined. We present some counterpoints to the redistricting proposal.